Profile and Trends of Community Morbidity in Mali from January 2018 to December 2019: A Cross-Sectional Study - Kalossi, Issa; Djiguiba, Adama; Traore, Hamadi; Somboro, Aboubacar Andre Pascal; Maiga, Almahamoudou Mahamadou (Universitas Brawijaya, 2025)
Abstract: The global burden of disease is dominated by non-communicable diseases, but for African and developing countries, infectious diseases and febrile syndromes are the most frequent. At the community level, the actual disease burden remains understudied. Aims: Our study aimed to determine the profile and trends of morbidity diagnosed at the community level and to determine the most frequent reasons for consultation in routine consultation. Methods: we conducted a cross-sectional and retrospective study on data from the CSCom consultation register in Nyamina. The data was collected using epi info 7 software and analyzed with R version 4 software. Results: at the end of our study, we recorded 8778 patients in routine consultation for 55.2% of women. Malaria was the most prevalent diagnosis with 68% followed by ARI 8%. While 75% of malaria cases occurred before the age of 20, non-communicable diseases such as hypertension were more common among the elderly. Conclusion: the morbidity profile was globally more dominated by communicable diseases, in particular malaria and ARI.